DAE solid state physics symposium during 2000–2010: a bibliometric perspective. (1st January 2014) - Prabhu, Anjali; Tiwari, Shalini; Swarna, T.; Bhanumurthy, K.
This study aims to analyse the conference proceedings – DAE Solid State Physics Symposium, an annual conference held since 1984 and sponsored by the Board of Research in Nuclear Sciences, Department of Atomic Energy, India. The factors studied are: the diversified venue and its impact on the number of conference presentations, the number of presentations in the fourteen subjects forming the domain of 'Solid State Physics' and the dynamic nature of these subjects; the authorship pattern during the period of study; the intra and inter regional authorship and collaboration pattern. The prominent international as well as national collaborating countries and institutes have been identified. The study revealed that major contributions were made by Indian universities and colleges.